2020
DOI: 10.1080/09638288.2020.1830190
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the quality of paid support for adults with acquired neurological disability: scoping review and thematic synthesis

Abstract: Purpose: Theoretically, individualised funding schemes empower people with disability (PWD) to choose high quality support services in line with their needs and preferences. Given the importance of support, the aim of this scoping review was to understand the factors that influence the quality of paid disability support for adults with acquired neurological disability. Methods: A comprehensive scoping review of the published literature from 2009-2019 was conducted on five databases: Medline, CINAHL, Embase, Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Their existing empathy may have been a factor that encouraged them to seek (and attain) employment as disability workers. Topping et al ( 2020 ) found that empathy and understanding are important attributes for disability support workers. In addition, during the focus groups, participants indicated they had prior personal experiences of interactions with people with disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their existing empathy may have been a factor that encouraged them to seek (and attain) employment as disability workers. Topping et al ( 2020 ) found that empathy and understanding are important attributes for disability support workers. In addition, during the focus groups, participants indicated they had prior personal experiences of interactions with people with disability.…”
Section: Discussionmentioning
confidence: 99%
“…Empathy is “the ability to share someone else's feelings or experiences by imagining what it would be like to be in that person's situation” (Cambridge University Press, 2022 ). Empathy is a vital skill for disability support workers because the presence of empathy may improve the quality of communication and relationships with service users, as well as the responsiveness of workers to the needs of service users (Batchelder et al, 2017 ; Collins et al, 2017 ; Neubauer, 2020 ; Topping et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with acquired neurological conditions who are eligible for NDIS funding often experience severe or profound levels of core activity limitations due to varying levels of cognitive, communication or physical impairments. 18 19 The breadth and severity of these impairments coincide with primary healthcare needs distinct from the rest of the population and increased health challenges that often fall to GPs for initial treatment and management. 11 Previous research has found that although people with acquired neurological disability are high users of GP services, 20–22 they are less likely to receive comprehensive care 22 23 including low frequency of preventive care practices.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the experience and education of DSWs are important, quality of support is dependent on a multitude of factors (Topping et al, 2020 ). To provide individualised person‐centred support, DSWs must learn the unique needs and preferences of the individual they are supporting (Fadyl et al, 2011 ; Gridley et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%